The souls of mixed folk : race, politics, and aesthetics in the new millennium - Elam, Michele (Stanford, Calif. : Stanford University Press, 2011)
The Souls of Mixed Folk examines representations of mixed race in literature and the arts that redefine new millennial aesthetics and politics. Focusing on black-white mixes, Elam analyzes expressive works-novels, drama, graphic narrative, late-night television, art installations-as artistic rejoinders to the perception that post-Civil Rights politics are bereft and post-Black art is apolitical. Reorienting attention to the cultural invention of mixed race from the social sciences to the humanities, Elam considers the creative work of Lezley Saar, Aaron McGruder, Nate Creekmore, Da.
Introduction : mixed race in the post-race era -- The mis-education of mixed race -- The "ethno-ambiguo hostility syndrome" of the "halfrican American" : mixed race in Aaron Mcgruder's The boondocks and Nate Creekmore's Maintaining -- Passing in the post-race era : Danzy Senna's Caucasia, Philip Roth's The human stain, and Colson Whitehead's The intuitionist -- People just like us : Emily Raboteau's The professor's daughter, Danzy Senna's Symptomatic, and the mixed race anti-Bildungsroman -- "They's mo to bein' black than meets the eye!" : performing mixed race in Dave Chappelle's "The racial draft" and Carl Hancock Rux's Talk.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: American literature -- 21st century -- History and criticism; Multiracial people in literature; African Americans in literature; Race in literature; Race relations in literature; Passing (Identity) in literature; Littérature américaine -- 21e siècle -- Histoire et critique; Noirs américains dans la littérature.; Race dans la littérature.; Relations raciales dans la littérature.; Passing (Identité) dans la littérature.; LITERARY CRITICISM -- American -- General; African Americans in literature; American literature; Passing (Identity) in literature; Race in literature; Race relations in literature; Multiracial people in literature; 2000-2099; Criticism, interpretation, etc